Work Enjoyment dan Organizational Citizenship Behavior pada Karyawan PT. Petrokimia Kayaku - Septiyan Nugroho; Ni Wayan Sukmawati Puspitadewi (Universitas Negeri Surabaya, 2015)
Organizational Citizenship Behavior is one form of behavior of employeesthat shows the tendency to be cooperative in an organization.This research holds a purpose to test the correlation between Work Enjoyment and Organizational Citizenship Behavior in PT Petrokimia Kayaku Gresik. This research used quantitative approach which focuses on correlational research design. The number of population in this research was 170 people and the samples obtained were 63 people that was selected using random sampling technique. Questionnaire was chosen as the way to collect the data needed in this research. There were two kinds of questionnaires whichwere developed by the researcher to determine Organizational Citizenship Behaviors scale and workenjoyments scale. The data analysis used was product moments correlation. According to the data analysis, there is a significant correlation between work enjoyment and Organizational Citizenship Behavior, with the correlation coefficient 0,861 and p = 0,000 that indicates high and significant correlation. Abstrak: Organizational Citizenship Behavior merupakan salah satu bentuk perilaku dari karyawan yang menunjukkan kecenderungan untuk koperatif dalam suatu organisasi. Penelitian ini bertujuan untuk mengetahui hubungan antara Work Enjoyment dengan perilaku Organizational Citizenship Behavior pada Karyawan PT Petrokimia Kayaku Gresik. Penelitian dilakasanakan dengan pendekatan kuantitatif dengan rancangan penelitian korelasional. Jumlah populasi pada penelitian ini sebesar 170 orang, sampel diambil dengan menggunakan random sampling sehingga didapat jumlah sampel sebanyak 63 orang. Pengambilan data pada penelitian ini menggunakan kuesioner yang dikembangkan oleh peneliti yaitu skala Organizational Citizenship Behavior dan skala work enjoyment. Analisis data menggunakan korelasi product moment. Berdasarkan hasil analisis data ada hubungan yang signifikan antara work enjoyment dengan Organizational Citizenship Behavior dengan